Indigenous music as moral pedagogy: a study of cultural transmission in South African folklore - Mdhluli, Nontokozo Gladys; Masipa, Masila Joshua (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study investigates the significance of indigenous music in African folklore as a vehicle for transferring cultural norms and values to African children, with a particular emphasis on its impact on moral and social development. The study's goal is to look at how traditional music genres, including lullabies, folk songs, chants, and storytelling, might serve as informal educational platforms for African children, shaping their ethical conduct, identity, and communal values. The study employs a qualitative research methodology, including ethnographic fieldwork, interviews with elders, cultural custodians, and educators, and an analysis of select indigenous songs from three African communities. Audio recordings and transcriptions of traditional music performances are studied thematically to reveal hidden messages and cultural values. The research is based on Social Learning Theory and Afrocentric Theory, both of which emphasize learning by observation, engagement, and conformity with African worldviews. These frameworks help us understand how children internalize moral norms and social expectations through cultural exposure. The findings show that indigenous music is still an effective cultural channel for promoting values like respect, communal living, honesty, and accountability. However, modernization, urbanization, and the impact of Western media all contribute to a fall in its use, according to the study. This study adds to scholarship by integrating musicology, education, and cultural studies to highlight the instructional potential of traditional music. It advocates incorporating indigenous music into formal education curricula and community-based learning activities to promote cultural preservation and moral growth.